The home of Mr. and Mrs. Dubé - Oates, Lynette (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Report on a Folklore field trip Mainland (La Grand Terre) March 10-14 1990 ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Report on a Folklore field trip Mainland (La Grand Terre) March 10-14 1990".